Access and referral to palliative care for patients with chronic heart failure: A qualitative study of healthcare professionals. Issue 9 (12th March 2020) - Singh, Gursharan K.; Ramjan, Lucie; Ferguson, Caleb; Davidson, Patricia M.; Newton, Phillip J.
Abstract: Background: Palliative care for individuals with chronic heart failure is recommended for improving patients' symptoms, function and overall quality of life. Despite this mandate, there is limited access and referral to specialist palliative care for individuals with chronic heart failure. Objectives: To explore healthcare professionals' perspectives on access to palliative care for patients with chronic heart failure, focussing on patient, provider and system factors. Methods: Cardiologists, palliative care specialists, heart failure nurses and palliative care nurses in acute and community care settings were interviewed using semi‐structured interviews. Purposive and snowball sampling methods were used for recruitment. Interview data were analysed using thematic analysis. The COREQ checklist guided data collection and reporting. Results: There were 15 participants in the study, and the majority were female. Participants included palliative medicine physicians, a palliative care nurse consultant, cardiologists, a general practitioner and advanced heart failure nurses. The themes derived from the thematic analysis centred on patient, provider and system factors impacting access and referral to palliative care in the context of chronic heart failure. The patient themes were (a) patient and family preconception of palliative care and (b) patient's clinical profile influences referral. The provider themes were (a) conflict, (b) making decisions and (c) education needs, and the system themes were (a) accessing services and resources and (b) improving the model of care. Conclusions: The patient's clinical profile, education needs of healthcare professionals and improving access to services and resources need to be considered to enhance palliative care access and referral as well as the interacting and influencing elements of the patient, provider and system.